2004
DOI: 10.1603/0022-2585-41.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Distributions of Adult Screwworms (Diptera: Calliphoridae) in the Panama Canal Area, Republic of Panama

Abstract: The distribution of screwworms, Cochliomyia hominivorax, (Coquerel) was studied in a seasonally moist lowland tropical forest in the Republic of Panama using a combination of field collections and satellite imagery. We found that different forest types could be distinguished and mapped using remotely sensed data. To determine the temporal and spatial distribution of flies, we collected flies coming to rotted liver at 82 sites in ten vegetation types (open areas, edge forest, dry scrub forest, forest succession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…The Amazon rain forest represents this putative geographic barrier. Because the screwworm inhabits the interface between savannah and forest borders (Thomas 1993, Phillips et al 2004, Garcia et al 2007, processes involved in this forest fragmentation and recover (Clapperton 1993, Haffer andPrance 2001) might be responsible for the observed geographic structure of screwworm populations.…”
Section: ) Neotropical Butterßiesmentioning
confidence: 99%
“…The Amazon rain forest represents this putative geographic barrier. Because the screwworm inhabits the interface between savannah and forest borders (Thomas 1993, Phillips et al 2004, Garcia et al 2007, processes involved in this forest fragmentation and recover (Clapperton 1993, Haffer andPrance 2001) might be responsible for the observed geographic structure of screwworm populations.…”
Section: ) Neotropical Butterßiesmentioning
confidence: 99%
“…() found no association between NWS cases and seasonality likely due to a minimal seasonality in climate in their study carried out in Panama; on the contrary, no clearly marked seasonality in the presence of NWS was noted in San Miguel de Los Bancos. Phillips, Welch, and Kramer () reported that flies were most abundant during the transition from wet to dry season. This hypothesis could not be confirmed here because San Miguel de Los Bancos has stable climatic conditions throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,12,[14][15][16][17][18] The likelihood of establishment was calculated by combining these three maps multiplicatively to identify areas with suitable conditions for pupal development and adult fly survival.…”
Section: Table 2 Detailed Process For Creation Of Final Likelihood Mmentioning
confidence: 99%